2022
DOI: 10.1002/iis2.12935
|View full text |Cite
|
Sign up to set email alerts
|

From System Architecting to System Design and Optimization: A Link Between MBSE and MDAO

Abstract: Optimization of system architectures can help deal with finding better system architectures in a large design space plagued by combinatorial explosion of alternatives. To enable architecture optimization, the design space should therefore be formalized into a numerical optimization problem, and it should be possible to quantitatively evaluate architecture alternatives. This paper presents a methodology for generating and modeling architecture design spaces using the Architecture Design Space Graph (ADSG), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In (Bussemaker et al, 2022) a methodology is proposed for linking Model-Based Systems Engineering (MBSE) and collaborative Multidisciplinary Design Analysis and Optimization (MDAO). This shall enable optimization as a means to handle systems with large design spaces and many multidisciplinary stakeholders.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In (Bussemaker et al, 2022) a methodology is proposed for linking Model-Based Systems Engineering (MBSE) and collaborative Multidisciplinary Design Analysis and Optimization (MDAO). This shall enable optimization as a means to handle systems with large design spaces and many multidisciplinary stakeholders.…”
Section: Related Workmentioning
confidence: 99%
“…This requires a problem break down in a formalized manner. The systems architecting phase is generally used to identify goals, specify scenarios and requirements in order to design a systems architecture (Bussemaker et al, 2022). For this, knowledge of existing system architectures and past projects is used as a starting point.…”
Section: Logical Architecturementioning
confidence: 99%
“…Last, a few current works can be found that exploit OR with systems engineering, but none of them mention architecture frameworks as best suited to represent the quantities of interests and classify information. First, 27 present algorithms that define a design space graph on which architecture decisions can be made in an iterative process, based on the metrics defined for the system category. There is also the well‐documented, 28 which uses surrogates to measure the interaction of an architecting team with its emerging systems.…”
Section: State‐of‐the‐art: Operation Research and Architecture Frameworkmentioning
confidence: 99%
“…The work presented in this paper has been performed as part of the EU-funded AGILE4.0 project, wherein the German Aerospace Center (DLR) lead the development of a Model-Based Systems Engineering (MBSE) framework for complex system design (Bussemaker, Boggero & Nagel 2023;Ciampa, Rocca & Nagel 2020). The framework consists of two consecutive and connected phases, an upstream architecting phase, and a downstream product design phase .…”
Section: Introductionmentioning
confidence: 99%